Improved ANN-based algorithm for detection and classification of faults on transmission lines - Fayaz, Farhana; Isa, Abubakar; Verma, H. K.; Deb, Soma (2016 1st India International Conference on Information Processing (IICIP), 2016)
This paper presents a relaying algorithm based on Artificial Neural Network (ANN) technique for the protection of transmission line. A feed forward ANN with six inputs and eleven outputs has been developed for the detection and classification of faults. Data was generated by simulating a 400 kV, 50Hz, 100 km transmission line in PSCAD/EMTDC at a sampling frequency of 2 kHz. Three ANN configurations with different combinations of inputs have been attempted. Initially all the three ANN configurations were trained and tested using truncated data for their comparative performance. ANN-2 configuration has been found to be the best one and has an accuracy of 100% for fault detection and classification in both training and testing phases with the relay operating time of 12.5 ms. ANN-2 has been further trained and tested using full data. Two-fold cross verification was carried out. An accuracy of 100% was obtained on testing with 12.5 ms delay each time.